2017
DOI: 10.3892/etm.2017.4766
|View full text |Cite
|
Sign up to set email alerts
|

3-n-Butylphthalide reduces the oxidative damage of muscles in an experimental autoimmune myositis animal model

Abstract: 3-n-Butylphthalide (NBP) protects the mitochondria and reduces apoptosis in multiple disease models. However, it remains to be determined whether NBP can protect muscle cells from oxidative stress, lipid peroxidation and apoptosis in myositis. In the present study, a myosin immunization protocol was applied to induce experimental autoimmune myositis (EAM) in guinea pigs. After 4 weeks, a low- or high-dose NBP solution was injected intraperitoneally into the guinea pigs, with saline solution serving as the nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…NBP also works against H 2 O 2 -induced injury in neural stem cells by activation of the PI3K/Akt pathway ( 22 ). NBP increases the superoxide dismutase and catalase activity and reduces malondialdehyde activity in experimental autoimmune myositis model ( 23 ). Despite the above findings, it is unclear how NBP regulates microglia in vitro and the mechanisms involved remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…NBP also works against H 2 O 2 -induced injury in neural stem cells by activation of the PI3K/Akt pathway ( 22 ). NBP increases the superoxide dismutase and catalase activity and reduces malondialdehyde activity in experimental autoimmune myositis model ( 23 ). Despite the above findings, it is unclear how NBP regulates microglia in vitro and the mechanisms involved remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…[74] In addition, in a similar model, studies also found that NBP can act as an anti-oxidant to protect muscle mitochondria and muscle cells from oxidative damage, by enhancing SOD and catalase activity, decreasing MDA activity, and enhancing ATPase activity on the mitochondrial membrane and muscle fiber membrane. [75] Further, in a mouse model of autoimmune myelitis, NBP was found to attenuate the progression of this disease by inhibiting phosphoglycerate mutase family member 5-induced necrosis and inflammation in microglia. [76]…”
Section: Butylphthalide and Autoimmune Diseasementioning
confidence: 99%
“…NBP also protects against H 2 O 2 -induced injury in neural stem cells by activation of the PI3K/Akt and the Mash1 signaling pathways (32). Furthermore, NBP has been reported to increase superoxide dismutase and catalase activity, and reduce malondialdehyde activity in the experimental autoimmune myositis (EAM) model, NBP directly protects muscle mitochondria and muscle cells from oxidative damage (33). However, the protective effect of NBP on mitochondrial function is not only limited to neurodegeneration, but also appears in cardiovascular diseases.…”
Section: Nbp Reduces Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…Another study demonstrated that NBP improves cognitive impairment of APP/PS1 mice by inhibiting apoptosis via the PI3K/AKT pathway (39). Additionally, NBP reduces the number of apoptotic cells by regulating Bcl-2 in HUVECs and an EAM model (22,33).…”
Section: Nbp Regulates Apoptosis and Autophagymentioning
confidence: 99%